132 ROLE OF THE SDF-1/CXCR4 AXIS IN EXPERIMENTAL OBLITERATIVE BRONCHIOLITIS. (1st January 2006) - Xu, J.; Mora, A. L.; Shim, H.; Joodi, R.; Ramirez, A.; Brigham, K. L.; Rojas, M.
Abstract : Long-term success in lung transplantation is limited by obliterative bronchiolits (OB) and the mechanism of this disease is not well understood. The chemokine SDF-1 (produced in injured tissues) and its receptor CXCR4 (present on progenitor cells) have been reported to contribute to lung fibrosis by recruiting progenitor fibrocytes to injured tissue. We hypothesized that the SDF-1/CXCR4 axis plays a role in the pathogenesis of OB and tested this idea in a mouse heterotopic allogeneic tracheal transplant model. We transplanted mouse tracheas from wild-type female Balb/c donors into C57BL/6 GFP+ male recipients. We found both GFP and Y chromosome positive cells in the lumen and epithelial layer of allografts on day 10 post-transplant. SDF-1 was highly expressed in cells in the subepithelial layers of the graft and the majority of cells infiltrated into the allograft lumen were CXCR4 positive. A CXCR4 antagonist, TN 14003, decreased the infiltration of CXCR4 positive cells into the allograft and significantly reduced epithelial loss on day 10 and luminal fibrotic occlusion on day 42 post-transplant (57.40% versus 98.21%, p < .01). We conclude that transplant-induced increased production of SDF-1 recruits host CXCR4 expressing cells to the tracheal allograft and that these cells contribute to both epithelial injury and later fibrosis. We speculate that inhibition of the SDF-1/CXCR4 axis may be a novel approach to prevention of transplantation-induced obliterative bronchiolitis.